Comprehensive rehabilitation program after knee arthroplasty of GMRS as a result of treatment of a chondrosarcoma of distal part of femur with pathological fracture of the lateral femoral condyle. - Anna Baranowska; Karina Szczypiór-Piasecka; Alicja Mińko; Krzysztof Antczak (Kazimierz Wielki University, 2021)
Abstract Introduction: Malignant neoplasms of bones and articular cartilage resulting from the operation of the mesenchymal sales cell valuation bank. Cells can differentiate in many countries. in. chondrocytes, osteoblasts or adipocytes The bone cancer that occurs is osteosarcoma. In second place is chondrosarcoma (chondrosarcoma). Materials and methods: The work was written based on the development of a patient who had the further development of the femur part of the former cartilage sarcoma radio station. The entire treatment procedure at the Department of Orthopedics, Traumatology and Oncology of the Musculoskeletal System, located at Unii Lubelskiej 1 street in Szczecin. Results: At the main point of treatment of the hospital clinic, the patient, the patient who returns as good working point, points to restore lost functions, as well as self-service learning. Conclusion: Rehabilitation is an indispensable carrier of services for cancer patients. Introducing modern techniques such as therapy and osteopathy to rehabilitation, ensuring the economy of therapy.